Sensitivity Analysis of Reinforced Concrete Deep Beam by STM and FEM (Part III). (2018) - Shariat, Mehran; Eskandari-Naddaf, Hamid; Tayyebinia, Morteza; Sadeghian, Mohammad
Abstract: The behavior of deep beams is significantly different from that of normal beams. Because of their proportions, deep beams are likely to have strength controlled by shear. This paper presents a strut-and-tie model (STM) to determine the strength of deep beams that were conducted experimental research in before researches, by using the ACI and ASHTO provisions. The behavior of the deep beams is investigated in failure mode that will happen in shear or flexural mode and so predict the total load that the beam can sustain. The gained load is verified with the exposed failure load in the laboratory. Comparison of the results obtained by using two standards that is closer to experimental data also conducted. Also there are several analytical tools available for analyzing deep beams. Among all the available analytical methods, finite-element analysis (FEA) by software's offers a better option. The results from this study were compared with results from renowned finite-element software (ABAQUS), and the results obtained were shown to reasonably agree.